Stability of Spatial Equilibrium. - Tabuchi, Takatoshi; Zeng, Dao-Zhi (Journal of Regional Science, 2004)
Asymptotic stability of equilibrium is often difficult to know when the number of variables exceeds four, since all eigenvalues of the Jacobian matrix are not analytically solvable. However, we obtain stability conditions for a general class of migration dynamics without computing eigenvalues. We show that a spatial equilibrium is stable in the presence of strong congestion diseconomies, but unstable in the presence of strong agglomeration economies. We also show existence of a stable equilibrium in the case of negligible interregional externalities, which is applicable to club goods, local public goods, and new economic geography. Reprinted by permission of the publisher.